PENGUATAN MASYARAKAT DALAM UPAYA MENGATASI STRES DAN KECEMASAN PADA MASA PANDEMI COVID 19 - Achmad Syukkur; Oda Debora; Sulistyono Sulistyono (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2021)
The Community Partnership Program activity "Community Strengthening in Efforts to Overcome Stress and Anxiety During the Covid 19 Pandemic Period" carried out at Pandansari Village, Poncokusumo District, Malang Regency is an activity aimed at cadres and community in the midst of the Covid 19 pandemic. The purpose of this activity is to help people deal with stress and anxiety which arise during COVID-19 pandemic so that public health can be optimized. Therefore, it is necessary to carry out and develop the capacity of the community and health cadres in the context of promotive and preventive efforts. Nurse is one of healthcare provider, so the stress management which is given is as holistic as possible, regarding the physical and psychological aspects. The evaluation of knowledge obtained through the pre-test and post-test showed that the average knowledge of the community increased from an average of 55 to an average of 91 and the evaluation for yoga activities could do 6 out of 10 yoga movements. Simple yoga training can be done in the community so that the community's health status can be improved.